Análisis y rediseño de la estructura financiera de la empresa inducarrerro s.a. (industria cárnica reyes romero), año 2011 - Álvarez Rodríguez, Mayra Susana (2012)
INDUCARRERO S.A., has many and varied problems one of which is the trend or limitation of utilities that force their different managers to overcome through the study and understanding of the company so that it can improve its performance, this in the current world in which we live requires adequate and timely financial information that must be quantitativereliable and accessible so that help strengthen their judgment or decision on any financial matter. The Finance Department serves as the planning of economic resources to make your application the way more optimal, in addition to researching the sources of funding for the acquisition of resources when an enterprise has need of them, seeks the reduction of uncertainty of investment, all this with the purpose of obtaining maximum earnings per share or the profitability of the company. The stock information that develop different areas of work must be delivered to the Finance Department for the summary and financial reporting, and therefore analyze the financial structure of the company, which are an essential tool for the decision-making process. INDUCARRERO S.A. Meets economic shortcomings therefore proposed an analysis and redesign of the financial structure of Inducarrero S.A. The stock information that develop different areas of work must be delivered to the Finance Department for the summary and financial reporting, and therefore analyze the financial structure of the company, which are an essential tool for the decision-making process.